2022
DOI: 10.1017/s003329172200112x
|View full text |Cite
|
Sign up to set email alerts
|

Associations of neuroimaging markers with depressive symptoms over time in middle-aged and elderly persons

Abstract: Background Cerebrovascular disease is regarded as a potential cause of late-life depression. Yet, evidence for associations of neuroimaging markers of vascular brain disease with depressive symptoms is inconclusive. We examined the associations of neuroimaging markers and depressive symptoms in a large population-based study of middle-aged and elderly persons over time. Methods A total of 4943 participants (mean age = 64.6 ± 11.1 years, 55.7% women) from the Rotterdam Study were included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…In model 2, we additionally adjusted for age 3 (as cubic function, meaning polynomial function of degree 3), age and sex interaction, smoking, asthma, COPD, clinically relevant depressive symptoms (CESD score, > 16), and chronic pain, given that they are prevalent in chronic cough, 17 , 20 , 22 and have been associated with volumetric brain changes in adults. 23 , 24 , 25 , 26 , 27 , 28 Furthermore, we estimated the annualized percentage volume decline rate, examined hemispheric lateralization, and performed stratified analyses for sex, focusing on brain regions that demonstrated statistical significance. We also explored the relationship between chronic cough phenotype (explained and unexplained) and regional brain volumes using multivariable linear regression models that were adjusted for potential confounding factors (models 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…In model 2, we additionally adjusted for age 3 (as cubic function, meaning polynomial function of degree 3), age and sex interaction, smoking, asthma, COPD, clinically relevant depressive symptoms (CESD score, > 16), and chronic pain, given that they are prevalent in chronic cough, 17 , 20 , 22 and have been associated with volumetric brain changes in adults. 23 , 24 , 25 , 26 , 27 , 28 Furthermore, we estimated the annualized percentage volume decline rate, examined hemispheric lateralization, and performed stratified analyses for sex, focusing on brain regions that demonstrated statistical significance. We also explored the relationship between chronic cough phenotype (explained and unexplained) and regional brain volumes using multivariable linear regression models that were adjusted for potential confounding factors (models 1 and 2).…”
Section: Discussionmentioning
confidence: 99%
“…A population-based study showed that reduced total brain volume, larger WMH volume, presence of cortical microinfarcts, and higher levels of mean diffusivity (indicating WM microstructural integrity) were cross-sectionally associated with higher depressive symptoms. These associations were more pronounced in older age, indicating that damage of WM structure might be crucial for the pathogenesis of LLD (Özel et al 2022 ). On the other hand, LLD accentuates cognitive weaknesses in older adults with small vessel disease (Oberlin et al 2022 ).…”
Section: Structural Brain Abnormalities In Lldmentioning
confidence: 99%
“…Firstly, the evaluation of depression is inconsistent. Some studies evaluate depressive symptoms [ 68 ], some use a self-report questionnaire to identify depressed individuals [ 69 ], and some undergo a structured clinical interview [ 1 , 22 ]. Importantly, these approaches may capture different ranges of depression severity.…”
Section: Challenges and Future Directions In The Identification Of Ll...mentioning
confidence: 99%